Impact of FDI on economic growth: The role of country income levels and institutional strength - Tamar Baiashvili; Luca Gattini (European Investment Bank (EIB), 2020)
Foreign direct investment (FDI) is generally considered a driving factor to economic growth. Nevertheless, empirical evidence is rather mixed, reporting a positive, neutral, or even negative relationship of FDI with growth. Our investigation concentrates on the impact of FDI inflows on growth and their effect mediated by income levels and the quality of the institutional environment. Specifically, we focus the interaction between country income levels - including low-, middle- and high-income countries - and FDI. This was not analysed thoroughly in earlier studies. Moreover, we deploy a new perspective to look into the FDI effects on growth mediated by institutional quality whereby we make use of country income levels as the key elements to peer-reference countries. Our study is based on 111 countries, stretching from developed economies to developing and emerging markets starting in 1980. Our estimations make use of panel GMM techniques robust to sample size, instrument proliferation and endogeneity concerns. We find that FDI benefits do not accrue mechanically and evenly across countries. We detect an inverted-U shaped relationship between countries' income levels and the size of FDI impact on growth. Moving from low to middle-income countries the effect gets larger. On the other hand, it diminishes again transitioning to high income countries. Finally yet importantly, we find that absorptive capacity matters in channelling FDI effects. Institutional factors have a mediating positive effect on FDI within country income groups, whereby countries with better-developed institutions relative to their income group peers show a positive impact of FDI on growth.
Keywords: C33; F21; E02; O43; O47; 330; Foreign Direct Investment (FDI); growth; income levels; institutions; absorptive capacity; global panel; Economics